Holocene glacier-climate history of the Calluqueo glacier and Monte San Lorenzo, central Patagonia - Peltier, Carly; Kaplan, Michael R.; Soteres, Rodrigo L.; Aravena Donaire, Juan Carlos; Sagredo, Esteban A.; Peccia, Ally; Schwartz, Roseanne; Amigo, Gonzalo; Schaefer, Joerg M. (My University, 2025)
We present 33 new Be-10 exposure ages on boulders rooted in moraines in the Calluqueo valley in central Patagonia. The former glacier flowed westward off the Monte San Lorenzo massif and was expanded from similar to 6,900 until similar to 6,700 years ago; and at 5,620 +/- 200, 5,140 +/- 150, 4,660 +/- 180, 4,100 +/- 140, 3,610 +/- 200, 3,120 +/- 110 years ago (n=2 for these groups), and repeatedly during the last similar to 600 years. Glaciers may have advanced earlier in the Holocene, but additional effort is needed to elucidate the timing. Also taking into account a record in the nearby Tranquillo Valley, we see that at Monte San Lorenzo glaciers were expanded often between similar to 7 and similar to 3 ka, and after similar to 1.4 ka. During the middle Holocene moraines were built on average every similar to 500 years. The largest expansions of the last millennium were at similar to 1400-1500 CE. We also date boulders on the innermost moraine terrain to 1810 CE +/- 20 and 1870 CE +/- 20 years. A last phase of stability existed from similar to 1800 to 1940 CE, with pronounced ongoing retreat since after 1940 CE. The Monte San Lorenzo chronologies allow us to compare Holocene records between central and southernmost Patagonia. Throughout Patagonia, there is a similar glacier-climate history, with nested moraine sets and the largest glaciers generally in the mid-early Holocene. In most places, a marked change in glacier behavior and climate occurred around 7 ka, but some sites exhibit evidence of earlier Holocene activity. Over the last millennium, a net decrease in extent of advances occurred from similar to 1400 to similar to 1800 CE. However, there are some differences across Patagonia. In central Patagonia (similar to 44-49 degrees S), glaciers expanded between 4 and 3 ka, while from 3 to 2 ka moraines are not preserved; the pattern appears reversed to the south (i.e. south of similar to 49 degrees S). We hypothesize that Subantarctic or high latitude climates strongly impacted at least as far as northern Patagonia throughout the Holocene, including centennial and millennial changes in cold phases reflecting shifts in the Southern Hemisphere Westerlies and associated air masses. One exception perhaps is between 4 and 3 ka, where moraines are not observed to the south, possibly reflecting closer proximity to Antarctica where this interval may be generally warm. Regardless of secondary differences across southern South America, glacier records in central Patagonia are unlike those in the Northern Hemisphere, but similar to other records in the Southern Hemisphere. For comparison, anthropogenic climate change has caused climate, and thus glacier, behavior to be more in sync between the hemispheres, whereas longer-term Holocene records show distinct differences in histories even regionally within South America.
Keywords: holocene; glaciation; paleoclimatology; south america; patagonia; ela; glacial geomorphology; be-10 exposure dating